Metabolite-protein interactions: Native mass spectrometry and collision induced affinity selection mass spectrometry in natural product screening - Gu, Yushu; Liu, Miaomiao; Quinn, Ronald J. (Frontiers in Analytical Science, 2022)
Understanding molecular level interactions between the metabolome and proteome, two of the most important classes of molecules in biology, will generate deeper insight into the function of metabolites (natural products) which have a central role in interactions with therapeutic targets. Drug discovery in today’s pharmaceutical environment is driven by high-throughput screening of large chemical libraries. It is now 10 years since we published a paper on the development of natural product fraction libraries with control of LogP properties. We have now turned our attention to using pure natural product libraries to address the timeframe issues associated with isolation and characterization of the active constituent(s). Native mass spectrometry can be used as a robust platform for identifying the interactions between natural products and their protein targets. The recent development of Collision-Induced Affinity Selection mass spectrometry, a technique using capture of ligand-protein complexes followed by collision induced dissociation to identify library hits followed by direct ligand-protein confirmation in native mass spectrometry also enables screening of a greater proportion of human proteins. We will review native mass spectrometry-based approaches to use natural product extracts, pre-fractionated natural product libraries and pure natural product libraries for screening against molecular targets. We will also discuss some of the other mass-spectrometry based applications that have been implicated in natural product drug discovery.